Giant extracellular Glossoscolex paulistus Hemoglobin (HbGp) upon interaction with cethyltrimethylammonium chloride (CTAC) and sodium dodecyl sulphate (SDS) surfactants: Dissociation of oligomeric structure and autoxidation - Santiago, Patricia S.; Moreira, Leonardo M.; de Almeida, Erika V.; Tabak, Marcel (Biochimica et biophysica acta, 2007)
The effects of two ionic surfactants on the oligomeric structure of the giant extracellular hemoglobin of Glossoscolex paulistus (HbGp) in the oxy - form have been studied through the use of several spectroscopic techniques such as electronic optical absorption, fluorescence emission, light scattering, and circular dichroism. The use of anionic sodium dodecyl sulphate (SDS) and cationic cethyltrimethyl ammonium chloride (CTAC) has allowed to differentiate the effects of opposite headgroup charges on the oligomeric structure dissociation and hemoglobin autoxidation. At pH 7.0, both surfactants induce the protein dissociation and a significant oxidation. Spectral changes occur at very low CTAC concentrations suggesting a significant electrostatic contribution to the protein–surfactant interaction. At low protein concentration, 0.08 mg/ml, some light scattering within a narrow CTAC concentration range occurs due to protein–surfactant precipitation. Light scattering experiments showed the dissociation of the oligomeric structure by SDS and CTAC, and the effect of precipitation induced by CTAC. At higher protein concentrations, 3.0 mg/ml, a precipitation was observed due to the intense charge neutralization upon formation of ion pair in the protein–surfactant precipitate. The spectral changes are spread over a much wider SDS concentration range, implying a smaller electrostatic contribution to the protein–surfactant interactions. The observed effects are consistent with the acid isoelectric point (pI) of this class of hemoglobins, which favors the intense interaction of HbGp with the cationic surfactant due to the existence of excess acid anionic residues at the protein surface. Protein secondary structure changes are significant for CTAC at low concentrations while they occur at significantly higher concentrations for SDS. In summary, the cationic surfactant seems to interact more strongly with the protein producing more dramatic spectral changes as compared to the anionic one. This is opposite as observed for several other hemoproteins. The surfactants at low concentrations produce the oligomeric dissociation, which facilitates the iron oxidation, an important factor modulating further oligomeric protein dissociation.